Anais De XXXVI Simpósio Brasileiro De Telecomunicações E Processamento De Sinais 2018
DOI: 10.14209/sbrt.2018.315
|View full text |Cite
|
Sign up to set email alerts
|

Novo protocolo de reconciliação de chaves secretas geradas quanticamente utilizando códigos LDPC no sentido Slepian-Wolf

Abstract: Resumo-Este artigo apresenta uma solução alternativa ao uso das funções Slice para reconciliação de variáveis aleatórias contínuas em um contexto de geração de chaves secretas para fins de criptografia. O protocolo de reconciliação proposto baseia-se na função distribuição de probabilidade das variáveis aleatórias e se mostra um método competitivo por sua capacidade de gerar a mesma quantidade de bits que o esquema atualmente em uso, com uma vantagem de menor iteratividade. O processo de correção de errosé fei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A much easier solution is proposed in [15] where it is performed a binary expansion of continuous values that acts as a quantizer method, ensuring expansion bits interdependence based on the following well known Lemma [20]: Fig. 2.…”
Section: A Quantization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A much easier solution is proposed in [15] where it is performed a binary expansion of continuous values that acts as a quantizer method, ensuring expansion bits interdependence based on the following well known Lemma [20]: Fig. 2.…”
Section: A Quantization Methodsmentioning
confidence: 99%
“…The complexity of extracting bits from the continuous variable is also high. Recently, a Binary Expansion Protocol has been proposed, relying on information theory arguments of probability distributions [15] presenting itself as a strong option over SEC reconciliation due to its random variable optimal compression rate.…”
Section: Introductionmentioning
confidence: 99%
“…Both SEC and MD reconciliation procedures present a way to extract bit sequences from continuous valued data so that an error correcting code could be applied, typically an LDPC code [10], [13], [15], [16]. A relatively recent alternative, proposed by Araújo and Assis [14] leverages a property of random variables with continuous distribution function widely used in Copula Theory [17], [18,Theorem 1.2.6].…”
Section: Distributional Transform Expansionmentioning
confidence: 99%
“…As the bits in the expansion are independent of each other, it is also possible that both Alice and Bob perform the DTE on their sequences and treat the errors between D i (X) and D i (Y ) as a transmission over a binary symmetric channel BSC(p i ), where p i is the transition probability. This approach were used in [14] were they showed that reconciliation can be obtained in the first two sub-channels with 4 • 10 4 sized LDPC codes in at most 40 decoding iterations with 4.5 dB SNR. Although, the analysis was restricted to CVQKD protocols with homodyne detection and reconciliation efficiency was not addressed.…”
Section: Distributional Transform Expansionmentioning
confidence: 99%
See 1 more Smart Citation